Analisis Kinerja Satuan Polisi Pamong Praja (Satpol PP) Kota Magelang Dalam Penanganan Pedagang Kaki Lima - Rian Destiningsih; Evi Lestari (Jurnal Ekonomi, 2020)
The Civil Service Police Unit is one of the local government officials tasked with enforcing regional regulations, maintaining public order and public peace. The Civil Service Police Unit is also an institution located in every Province as well as Regency and City. The Magelang City Civil Service Police Unit is faced with various problems of order, especially Street Vendors (PKL). Street vendors have become commonplace in big cities. The purpose of this study is to provide an overview of how the performance of Satpol PP in Magelang City and how the impact or consequences of Satpol PP's actions in handling street vendors. The method used is a case study with a qualitative approach by means of purposive sampling. Data collection techniques used are interviews, observation, and study documentation. The results of this study indicate that the performance of the Magelang City Satpol PP is quite good. The performance of the Satpol PP is said to be good in terms of accountability, effectiveness, efficiency and performance responsibility of the Magelang City Satpol PP employees who have tried to deal with street vendors.